Exploring young people's perspectives of inequalities in health: a qualitative study. (20th October 2021) - Fairbrother, H; Crowder, M; Dodd-Reynolds, C; Egan, M; Er, V; Goyder, E; Griffin, N; Holding, E; Lock, K; Scott, S; Summerbell, C; Woodrow, N
Abstract: Background: Reducing inequalities in health is an enduring global public health challenge. Worryingly in England, inequalities across some groups and places are worsening, highlighted and exacerbated by the Covid-19 pandemic. While there has been growing interest in exploring public understandings of health inequalities, few studies have explored the views of young people. Our study seeks to redress this by exploring young people's perspectives of inequalities in health. Methods: Working with existing youth organisations, we recruited young people (aged 13-21) from six youth groups in areas of high deprivation across three geographical locations in England. Each group took part in three interlinked focus groups (n = 18), the majority of which were run online using video conferencing platforms. Focus groups were co-delivered with partnering youth organisations during 2021. They involved participatory concept mapping activities, and the discussion of health related news articles. Results: Key themes emerged around young people's perspectives of: i) factors influencing health within their local area; ii) understandings of inequalities in health; and iii) key messages to convey to those with a role in addressing health inequalities at a place level. Conclusions: Our study highlights the importance of exploring and understanding young people's perspectives of inequalities in order to better shape policies which are supported by the communities and people they impact. Key messages: Young people have a nuanced, experiential understanding of key factors influencing their health and inequalities in health within their local areas. Building upon young people's understandings of inequalities in health provides opportunities to mobilise support for policies seeking to change the distribution of key social determinants.